GPR41 modulates insulin secretion and gene expression in pancreatic β‐cells and modifies metabolic homeostasis in fed and fasting states. Issue 11 (22nd August 2016) - Veprik, Anna; Laufer, Dana; Weiss, Sara; Rubins, Nir; Walker, Michael D.
ABSTRACT: Insulin secretion by pancreatic β‐cells is primarily regulated by glucose; however, hormones and additional nutrients, such as long‐chain fatty acids, also play an important role inadjusting insulinoutput to physiologic needs. To examine the role of short‐chain fatty acids (SCFAs) in β‐cell function, we analyzed mouse models of gain and loss of function of GPR41 (FFAR3), a receptor for SCFAs, vs. wild‐type control mice. GPR41 gain of function [GPR41‐ overexpressing transgenic (41 Tg) model] and GPR41 loss of function [GPR41‐knockout (KO 41) model] resulted in complementary changes in glucose tolerance, without significant effects on insulin sensitivity. KO 41 mice showed fasting hypoglycemia, which was consistent with increased basal and glucose‐induced insulin secretion by islets in vitro . Mirroring this, 41 Tg islets showed impaired glucose responsiveness in vitro . Microarray analysis of islets from 41 Tg mice indicated significant alterations in gene expression patterns; several of the altered genes were chosen for further analysis and were also observed to change upon incubation of islets and cultured β‐cells with SCFAs in a GPR41‐dependent manner. Taken together, our results indicate that GPR41 and its ligands, SCFAs, may play an important role inthefine‐tuning of insulin secretion in fed and fasting states.—Veprik, A., Laufer, D., Weiss, S., Rubins, N., Walker, M.D. GPR41 modulates insulin secretion andgene expression in pancreatic β‐cells and modifies metabolic homeostasis in fed and fasting states. FASEB J. 30, 3860–3869 (2016) www.fasebj.org